USULAN SISTEM PENERIMAAN TANDAN BUAH SEGAR (TBS) DI PT X UNTUK MENGURANGI LOSESS TBS PADA LOADING RAMP DENGAN DISCRETE EVENT SIMULATION - A. Bagus Diva Megadana, A.
PT X is a company engaged in the palm oil plantation and processing industries. One of the operational activities at PT X is the inventory receiving of FFB (Fresh Fruit Bunche). This activity includes the weighing of FFB, grading of FFB, and the process of entering FFB into the loading hopper. At one of PT X's mills, Mill H, a problem was identified with a significant amount of FFB being crushed by transport vehicles. This issue has led to losses for the company. The study's background is based on FFB losses occurring at the loading ramp, with estimated losses up to hundreds of thousands of rupiah per day. Improving the FFB receiving system has become the focus of this research. The study aims to find a receiving system that can reduce FFB losses and provide a storage facility that offers protection for the FFB. Besides FFB losses, the waiting time for external dump trucks is also a concern for PT X, considering that external parties contribute to the company’s profits.